2011
DOI: 10.1177/1536504211418455
|View full text |Cite
|
Sign up to set email alerts
|

Inside the Wisconsin Occupation

Abstract: Walker announced the bill on a Friday (a traditional tactic to minimize news coverage) and planned an expedited debate so that the bill might pass within a week. Thanks, though, to some advance planning by union activists, it didn't quite work out that way. Back in December 2010, our union, the TAA, was anxious about the upcoming budget and possible cuts to university funding. We sent Facebook invitations encouraging students to deliver Valentine's Day cards to the governor that read, "I n UW: Governor Walker,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Many have observed that the “Wisconsin Uprising” resonated with revolts erupting around the globe in 2010–2011 (Acar et al :55; Collins ; Goldberg ; Hardt ). Yet state, military, and police efforts to “manage” protester bodies across these sites differed significantly.…”
Section: Introductionmentioning
confidence: 99%
“…Many have observed that the “Wisconsin Uprising” resonated with revolts erupting around the globe in 2010–2011 (Acar et al :55; Collins ; Goldberg ; Hardt ). Yet state, military, and police efforts to “manage” protester bodies across these sites differed significantly.…”
Section: Introductionmentioning
confidence: 99%